Lady and the Tramp : junior novelization - Rudnick, Elizabeth (Los Angeles : Disney Press, 2020)
An unlikely romance brews when a shy golden spaniel from Park Avenue falls in love with a mongrel from the wrong side of town.
At head of title: Disney.
"Based on the screenplay by Andrew Bujalski and Kari Granlund. Produced by Brigham Taylor, p.g.a. Directed by Charlie Bean."
Keywords: Dogs -- Juvenile fiction; Pets; Animals; Dogs -- Fiction